AN INVESTIGATION INTO THE USE OF METAPHOR IN ENGLISH AND VIETNAMESE PROVERBS RELATING TO POVERTY AND WEALTH - Assoc.Prof.Dr.TRƯƠNG VIÊN (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Study the linguistic and cultural features of the metaphorical expressions in English and Vietnamese proverbs relating to Poverty and Wealth; Help the learners of English and Vietnamese understand and love proverbs more by analyzing the linguistic and cultural features of those metaphorical expressions.